PELATIHAN KEMAMPUAN BAHASA INGGRIS DAN LITERASI DI KALANGAN ANAK-ANAK LOKAL DI OPEN FLOW LEARNING CENTRE - I Komang , Sulatra,; Ni Made Sinta , Dewi, (Fakultas Bahasa Asing, 2024)
English is an international language that plays a vital role in global communication, scientific development, and cross-cultural interaction. This research aims to investigate the factors influencing English language proficiency and literacy among local children participating in the English class program at Open Flow Learning Centre. The challenges of developing English skills among local children, especially in non-English-speaking environments, are a central focus. The study utilized observational methods, identifying factors like resource accessibility, appropriate teaching methods, social support, and cultural barriers as primary influences. The research underscores the importance of integrating English into daily activities and innovative approaches, including technology, to enhance motivation and learning outcomes. The findings contribute to a better understanding of educators' efforts to advance English language proficiency and literacy among local children, preparing them to face the complexities of a global future.